PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU (STUDI KASUS SEKOLAH DASAR NEGERI 3 BEBENGAN KECAMATAN BOJA) - Novita Wulandari; Noor Miyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem regarding the transformational leadership of school principals is regarding teacher performance, namely in terms of teachers' lack of attention in making PTK, as evidenced by the eight teachers, only 1 teacher was active in making PTK, even though in making this PTK the teacher could maximize his performance by evaluating the results. obtained so that teacher performance can be maximized, especially in terms of teaching in class. The job of most school principals is still only as a punisher, not as a guide, because giving punishment does not necessarily have a significant effect on the level of teacher absenteeism, even though by providing positive guidance to teachers, teachers become closer and more comfortable with this behavior, which in the end all teachers are conscious in their actions. Then the problem is that school principals are less appreciative of increasing competency development for teachers so that teachers' teaching methods are still focused on the previous model, ignoring the real conditions in the field. The implication of this research is that the principal's transformational leadership on teacher performance is to improve the quality of student education in the Bebengan 3 State Elementary School (SD) environment. If the leadership used by the principal increases, it can be ensured that teacher performance will also increase, thus having an impact on the quality of education produced.